2020
DOI: 10.3390/ijms21051592
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genome-Wide Approaches to Activity-Dependent Translational Control in Neurons

Abstract: Activity-dependent regulation of gene expression is critical in experience-mediated changes in the brain. Although less appreciated than transcriptional control, translational control is a crucial regulatory step of activity-mediated gene expression in physiological and pathological conditions. In the first part of this review, we overview evidence demonstrating the importance of translational controls under the context of synaptic plasticity as well as learning and memory. Then, molecular mechanisms underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 141 publications
(167 reference statements)
0
3
0
Order By: Relevance
“…Neuronal activity has been shown to induce numerous changes in neurons, including broad transcriptional and translational changes (Choe and Cho, 2020;Flavell and Greenberg, 2008;Yap and Greenberg, 2018), providing many other candidates to induce adaptive myelination. For example, as with synaptic transmission, transmembrane proteins could induce effects with high spatial specificity, particularly if their expression is restricted to the structure that is to be myelinated (or not myelinated).…”
Section: Other Neuronal Molecular Cuesmentioning
confidence: 99%
“…Neuronal activity has been shown to induce numerous changes in neurons, including broad transcriptional and translational changes (Choe and Cho, 2020;Flavell and Greenberg, 2008;Yap and Greenberg, 2018), providing many other candidates to induce adaptive myelination. For example, as with synaptic transmission, transmembrane proteins could induce effects with high spatial specificity, particularly if their expression is restricted to the structure that is to be myelinated (or not myelinated).…”
Section: Other Neuronal Molecular Cuesmentioning
confidence: 99%
“…Though ribosomopathies have consequences throughout the body, some ribosomal subunit mutations are connected specifically to neurological disorders, such as those linked to cases of Autism Spectrum Disorder (ASD) and intellectual disability (ID) (Hetman and Slomnicki, 2019;Choe and Cho, 2020). Defects in ribosome function have also been connected to neurodegenerative diseases such as Alzheimer's disease (AD) (Ding et al, 2005;Hernández-Ortega et al, 2016) and Parkinson's disease (PD) (Taymans et al, 2015), and ribosomal frameshifting is implicated in repeat expansion disorders such as Huntington's disease (HD) and Amyotrophic Lateral Sclerosis (ALS) (Gao et al, 2017).…”
Section: Protein Synthesis Linked To Neurological Diseasementioning
confidence: 99%
“…Recent studies have shown that aberrant lncRNA expression is implicated in multiple human diseases ranging from neurodegenerative diseases to cancers. Furthermore, the homeostasis and plasticity of neuronal signaling are required for sophisticated gene regulatory mechanisms [ 10 ]. Given the important roles of lncRNAs in gene regulation and tissue homeostasis, the findings suggest that lncRNAs play critical roles in neurodegeneration in RIR injury.…”
Section: Introductionmentioning
confidence: 99%